2018
DOI: 10.2116/analsci.17p483
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Mist Generation Assist Argon-Nitrogen Mix Gas Effect on Radioactive Strontium Quantification by Online Solid-Phase Extraction with Inductively Coupled Plasma Mass Spectrometry

Abstract: N2-Ar mix gas effect can easily improve the sensitivity of ICPMS; however, this effect discriminates against Sr. In this study, it was found that N2-Ar mixed gases introduced into nebulizing gas enhanced the sensitivity of online solid-phase extraction (SPE) with inductively coupled plasma mass spectrometry (ICPMS) for radioactive strontium quantification. An ultrasonic nebulizer (USN) improved the N2-Ar mixture gases effect of Sr and the mix gases (with USN) enhanced 3.7-times signal intensity of Sr in normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…The introduction of the N 2 -Ar mixed gas into the nebulizer enhanced sensitivities by more than 3.7 fold for 90 Sr measurement. 7 A limit of detection (LOD) of 0.3 Bq/L (0.059 pg/L) within 30 min was obtained by the composite use of these techniques. [5][6][7] Previous reports have demonstrated the applications of the cascade ICP-MS system for 90 Sr quantification in groundwater, rainwater, and solid samples.…”
Section: Analytical Sciencesmentioning
confidence: 99%
See 2 more Smart Citations
“…The introduction of the N 2 -Ar mixed gas into the nebulizer enhanced sensitivities by more than 3.7 fold for 90 Sr measurement. 7 A limit of detection (LOD) of 0.3 Bq/L (0.059 pg/L) within 30 min was obtained by the composite use of these techniques. [5][6][7] Previous reports have demonstrated the applications of the cascade ICP-MS system for 90 Sr quantification in groundwater, rainwater, and solid samples.…”
Section: Analytical Sciencesmentioning
confidence: 99%
“…[5][6][7] Previous reports have demonstrated the applications of the cascade ICP-MS system for 90 Sr quantification in groundwater, rainwater, and solid samples. [5][6][7][8][9] However, the introduction of a large amount of the matrix material into the ICP-MS system, due to multiple measurements of the samples containing the matrix material, causes considerable loss of sensitivity and necessitates the cleaning of the inner parts such as cones and DRC. This probrem, which has been actually faced, should be easily observed in analysis with several grams of marine products because the allowable limit of salt concentration in the samples is <1000 mg/L.…”
Section: Analytical Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon considering the impact of analytical procedures to the environment, sample preparation was found to be the most challenging step regarding the green parameters of a method. Solid-phase extraction was commonly used in the extraction of organic [2][3][4][5][6] and inorganic [7][8][9] contaminants from aqueous samples. It is also considered to be the main source of laboratory chemical waste.…”
Section: Introductionmentioning
confidence: 99%
“…Furukawa et al reported on "Ultrasonic Mist Generation Assist Argon-Nitrogen Mix Gas Effect on Radioactive Strontium Quantification by Online Solid-Phase Extraction with Inductively Coupled Plasma Mass Spectrometry", describing a radioactive strontium quantification. 7 They found that the sensitivity of online SPE with ICP-MS was enhanced by introducing Ar-N2 mixed gases as nebulizing gas, and measured environmental paddle water in Fukushima Nuclear Power Plant.…”
mentioning
confidence: 99%